On the selection by MCDM methods of the optimal system for seismic retrofitting and vertical addition of existing buildings. (15th October 2015) - Formisano, Antonio; Mazzolani, Federico M.
Highlights: Seismic retrofitting and vertical addition of existing buildings have been investigated. Different alternatives have been proposed for the two structural modification interventions. The TOPSIS MCDM method has been used for selecting the best alternative. Sensitivity analyses have proved the objectivity of the solutions found. Abstract: In the current paper a novel procedure to select the optimal solution both for seismic retrofitting of existing RC buildings and for super-elevation of existing masonry constructions has been implemented by using three different Multi-Criteria Decision Making (MCDM) (TOPSIS, ELECTRE and VIKOR) methods. The procedure application has been faced with reference to two case studies. The first intervention has been studied on a real full-scale 3D RC structure retrofitted with different seismic protection devices mainly based on metal materials, whose performances were experimentally evaluated in a previous research project. All the applied MCDM methods have provided the same result, that is the dominating role exerted by aluminium shear panels for seismic retrofitting of the analysed structure. On the other hand, different innovative and traditional constructive systems have been examined to increase the number of floors of existing masonry buildings. The effectiveness of these interventions in improving the base building behaviour has been proved on a typical building of the South Italy. The study results, achieved by using the three MCDM methods inspected, have provided as an optimal solution the cold-formed steel systems thanks to their prerequisites of lightness, economy and sustainability.